Discordant human epidermal growth factor receptor 2 overexpression in primary and metastatic upper gastrointestinal adenocarcinoma signifies poor prognosis. Issue 2 (16th July 2015) - Hedner, Charlotta; Tran, Lena; Borg, David; Nodin, Björn; Jirström, Karin; Eberhard, Jakob
Abstract : Aims: Targeted therapy with trastuzumab has proved to be effective for patients with gastric cancer overexpressing the human epidermal growth factor receptor 2 (HER2). Further studies are needed to determine the best method for assessment of HER2 overexpression. Moreover, the prognostic value of HER2 overexpression, including the significance of tumour heterogeneity, remains unclear. Methods and results: HER2 overexpression and gene copy alterations were assessed by immunohistochemistry and silver in‐situ hybridization, respectively, on tissue microarrays with primary tumours and a subset of paired lymph node metastases from 174 patients with oesophageal or gastric adenocarcinoma. Cox proportional hazards modelling was applied to assess the prognostic impact of HER2 overexpression, intratumoural heterogeneity and conversion from primary tumour to metastasis. The correlation between protein expression and gene amplification was in line with previous studies. Primary–metastatic conversion was observed in 12.9% of the cases. HER2 overexpression or intratumoural heterogeneity was not prognostic, but primary–metastatic conversion was an independent predictor of a shorter overall survival (hazard ratio = 4.93). Conclusions: As trastuzumab is emerging as an important targeted therapy for patients with upper gastointestinal cancer, these results underline the importance of further studies addressing the occurrence and clinical significance of discrepant HER2 expression in primary tumours and metastases.